A regional inter‐disciplinary partnership focusing on the development of a carinata‐centered bioeconomy. Issue 7 (4th May 2021) - George, Sheeja; Seepaul, Ramdeo; Geller, Dan; Dwivedi, Puneet; DiLorenzo, Nicolas; Altman, Rich; Coppola, Ed; Miller, Stephen A.; Bennett, Rick; Johnston, Glenn; Streit, Leon; Csonka, Steve; et al.
Abstract: Brassica carinata or Ethiopian mustard, a non‐edible oilseed brassica, is a low carbon, purpose‐grown, and none‐to‐low indirect land‐use change bioenergy feedstock for the production of drop‐in sustainable aviation fuel, biodiesel, renewable diesel, and a suite of value‐added coproducts. Carinata oil converted to drop‐in fuel using an American Society for Testing and Materials approved Catalytic Hydrothermolysis process has been successfully tested in commercial and military aviation. Carinata meal, the residue after oil extraction, is a high‐protein feed supplement for livestock, poultry, and swine, and can also yield specialty products. The Southeast Partnership for Advanced Renewables from Carinata (SPARC) is a public–private partnership formed with a twofold mission: (1) Removing physical, environmental, social, and economic constraints that prevent regional intensification of carinata production as a low‐carbon feedstock for renewable fuel and coproducts and (2) demonstrating enhanced value across the entire value chain by mitigating risk to farmers and other stakeholders. The partnership's goal is to energize the US bioeconomy through sustainable agriculture and thus contribute to energy security and economic diversification. SPARC relies on a combination of cutting‐edge multidisciplinary research and active industry engagement to facilitate adoption of the crop. This involves informing stakeholders along the entire supply chain, from producers to end‐users, policymakers, influencers, and the public, about the opportunities and best practices related to carinata. This article provides context and background concerning carinata commercialization as a winter cash crop in the Southeast US for renewable fuels and bioproducts. The advances made to date in the areas of feedstock development, fuel and coproduct development, meal valorization, supply chain logistics, and stakeholder engagement are outlined. Abstract : This article highlights the importance of Brassica carinata as a low carbon, nonfood, purpose‐grown oilseed that has tremendous potential to meet the demands of sustainable aviation fuel, valuable renewable co‐products and high protein feed in the US. In this context the paper highlights the accomplishments of a USDA‐NIFA funded coordinated agricultural project titled Southeast Partnership for the Advanced Renewables of Carinata.